2010
DOI: 10.1007/s00439-010-0938-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families

Abstract: Autosomal dominant woolly hair (ADWH) is an inherited condition of tightly curled and twisted scalp hair. Recently, a mutation in human keratin-74 (KRT74) gene has been shown to cause this form of hereditary hair disorder. In the present study, we have described two families (A and B) having multiple individuals affected with autosomal dominant form of hair loss disorders. In family A, 10 individuals showed ADWH phenotype while in the family B, 14 individuals showed hypotrichosis of the scalp. Genotyping using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…In addition, some families with ADWH/hypotrichosis may carry mutations in a type I keratin partner of K71, as mutations in two IRS-specific type I keratin genes, keratin K25 (KRT25) and keratin K27 (KRT27), have been reported to cause wavy coat phenotype in mice (Tanaka et al, 2007). The affected girl with the KRT71 mutation showed symptoms in both scalp hairs and facial hairs (Figure 1b and c), whereas all KRT74 mutations reported to date showed an obvious phenotype in scalp hairs alone (Shimomura et al, 2010b;Wasif et al, 2011), suggesting that KRT71 mutations can exhibit a more severe phenotype than KRT74 mutations. This may be because K71 is expressed in all three layers of the IRS, whereas K74 expression is restricted to the Huxley layer (Langbein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some families with ADWH/hypotrichosis may carry mutations in a type I keratin partner of K71, as mutations in two IRS-specific type I keratin genes, keratin K25 (KRT25) and keratin K27 (KRT27), have been reported to cause wavy coat phenotype in mice (Tanaka et al, 2007). The affected girl with the KRT71 mutation showed symptoms in both scalp hairs and facial hairs (Figure 1b and c), whereas all KRT74 mutations reported to date showed an obvious phenotype in scalp hairs alone (Shimomura et al, 2010b;Wasif et al, 2011), suggesting that KRT71 mutations can exhibit a more severe phenotype than KRT74 mutations. This may be because K71 is expressed in all three layers of the IRS, whereas K74 expression is restricted to the Huxley layer (Langbein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As both genes are abundantly expressed in the human HFs, particularly in the IRS, PA-PLA 1 a/LPA/LPA6 signaling is believed to play a crucial role in HF development and hair growth in humans (Shimomura et al, 2008(Shimomura et al, , 2009a. More recently, heterozygous mutations in the keratin K74 (KRT74) gene, also known as K6irs4, have been reported to underlie ADWH (OMIM 194300) (Shimomura et al, 2010b) and associated hypotrichosis (hypotrichosis simplex of the scalp 2; OMIM 613981) (Wasif et al, 2011). The KRT74 gene encodes type II epithelial keratin K74, which is predominantly expressed in the Huxley layer of the IRS (Langbein et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of human genes encoding hair-specifi c PAD substrate proteins are reported to be associated with human hair morphology (straight, wavy, or curly) as well as with disorders of hair loss (Shimomura 2012 ). Heterozygous mutations in IRS keratins (K71 and K74) are reported to cause autosomal dominant woolly hair (Wasif et al 2011 ;Fujimoto et al 2012 ), and TCHH gene variants are reported to be associated with hair morphology (Medland et al 2009 ). Although some deiminated proteins have emerged as key targets of the immune response in rheumatoid arthritis (Suzuki et al 2007 ), no direct evidence indicating an association of protein deimination with human hair morphology and disease has yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that WH is frequently associated with hypotrichosis. Recently, heterozygous mutations in KRT74 and KRT71 genes have been identified in families with ADWH/hypotrichosis ( Figure 7) [22][23][24]. Importantly, the KRT74 and the KRT71 genes encode the IRS-specific type II epithelial keratins K74 and K71, respectively ( Figure 8) [25].…”
Section: Current Genetics In Dermatologymentioning
confidence: 99%